The Influence Of Workload And Communication On Employee Performance In The Indramayu Class Iii Port Organization Unit Office - Pepen Efendi; Sri Astuti Pratminingsih; Reiza D. Dienaputra (Jurnal Ekonomi, 2024)
This research aims to analyze the influence of workload and communication on employee performance at the Class III Port Management Unit Office of Indramayu Regency. Using a quantitative approach, the research involved 34 respondents using a total sampling technique. Hypothesis test results show that workload and communication have a significant effect on employee performance. Workload (X1) has a significance value of 0.01, which is smaller than the probability of 0.05, so the hypothesis that workload affects performance is accepted. Likewise, organizational communication (X2) has a significance value of 0.04, also smaller than the probability of 0.05, so the hypothesis that communication influences performance is accepted. Further testing by comparing the calculated t and t table values confirms this result: workload with a calculated t of 4.142 is greater than a t table of 1.696, and communication with a calculated t of 2.056 is greater than a t table of 1.696, so both hypotheses are accepted. Thus, workload and communication are proven to have a positive effect on employee performance at the Class III Indramayu Port Management Unit Office.